Fiduciary Transfer of Ownership in Order to Secure the Satisfaction of Claim to Contemporary Right - Proposal De Le Lege Ferenda - Salihu, Ekrem (European Journal of Multidisciplinary Studies, 2019)
Fiduciary transfer of ownership in order to secure the claim satisfaction represents the form of non-possessory securing of claim satisfaction, which is experiencing the Renaissance in the transition countries and in the contemporary right. This form of non-possessory pledge right is not regulated by law in our own right, nor does it enjoy legal protection. Fiduciary transfer of property on the contemporary right and legal circulation is experiencing affirmation because of the essential advantages in relation to the real means of securing the claim satisfaction. The most important advantage of fiduciary agreements in relation to the pledge (mortgage) is the efficiency of the fulfilment of the claims, because there are no extensively long court proceedings in this institution. In addition to the fiduciary agreement, unlike the pledge right, the object that is subject to the fiduciary agreement, the debtor may keep such property under possession and may use it for the fulfilment of the obligations towards the creditor, thus offering practical benefits to the debtor itself. In the Republic of Kosovo, fiduciary agreements and fiduciary transfer of ownership are not regulated at positive rates. The author of this paper is committed to regulate this legal institute with positive provisions, i.e. the issuance of a special law for this institute, or the same to be included in the new Civil Code of Kosovo, as it is about an institute which has been applied for a long time by countries of the continental system and is experiencing renaissance also in the countries of the region (Slovenia, Macedonia, Montenegro, Croatia). The regulation of this institute with positive provisions would have a positive effect on legal circulation and faster economic development in Kosovo. At the same time, regulation of this institute with positive provisions would enable alignment and approximation of the Kosovo legislation with the European Union legislation. In this paper we will present the reasons why this institute should be regulated by special law or incorporated in the new Civil Code of Kosovo. However, despite the fact that local positive provisions do not particularly regulate the fiduciary transfer of ownership institution in order to secure the satisfaction of claim, nevertheless, this institute is not entirely excluded. Thus, the Law on Obligational Relationship of the Republic of Kosovo, in Article 429 provides for the ceding in order to secure "Where ceding is made in order to secure the claim satisfaction of the concessionaire against the cedant, the concessionary is obliged to behave with the care of a good economist, namely of a good housekeeper on the collection of ceded application and after the collection is completed, after keeping as much as it is needed to meet its demands against the cedant, shall hand him over the surplus.
Keywords: Fiduciary, Fiduciary ownership, Fiduciary transfer of ownership, pledge (mortgage) right.